Pelatihan Penerapan Lingkungan Kerja Bersih dan Aman, Sesuai Prinsip Keselamatan dan Kesehatan Kerja (K3) untuk Meningkatkan Usaha Massage dan Lulur - Agus Susanti (ABDI KARYA : Pengabdian Kepada Masyarakat, 2025)
The training program on implementing a clean and safe work environment, based on Occupational Safety and Health (OSH) principles, is a crucial initiative aimed at enhancing service quality in the massage and body scrub industry. Conducted in collaboration with Mardi Utomo Social Service Institution, this training is part of a community service program designed to educate participants on creating a hygienic and OSH-compliant workplace. The primary objective of this program is to equip participants with both theoretical knowledge and practical skills in maintaining a safe, clean, and health-conscious work environment. Adhering to OSH principles plays a vital role in mitigating workplace hazards, improving service quality, and ensuring customer satisfaction. By fostering a hygienic and secure setting, this training aims to reduce work-related risks and enhance the overall comfort and safety of clients. The training methodology involved a combination of interactive lectures, group discussions, Q&A sessions, and periodic evaluations, which contributed to a deeper understanding of the significance of OSH among the participants. The outcomes of the training demonstrated an increase in participants' awareness of OSH's importance, as well as positive changes in their behaviors towards cleanliness and safety practices. These behavioral adjustments are expected to establish a more professional and responsible work culture, ultimately increasing customer confidence in the services provided. With the implementation of these OSH standards, the massage and body scrub industry can continue to thrive, ensuring long-term sustainability. By fostering a work environment that adheres to health and safety guidelines, businesses in this sector can improve service quality, attract more clients, and ensure the well-being of both employees and customers.